Pedagogical and Cultural Competence Work Islamic Religious Education Teachers in Improving Character Student At State High School in Rantau Selamat District - Zuraida Zuraida; Amiruddin Amiruddin; Yusaini Yusaini (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study aims to 1) analyze the pedagogical competence of Islamic Religious Education teachers in the learning process at State Senior High Schools in Rantau Selamat District. 2) analyze the work culture of Islamic Religious Education teachers contributing to the formation of student character at State Senior High Schools in Rantau Selamat District. 3) analyze the supporting and inhibiting factors in the implementation of pedagogical competence and work culture of Islamic Religious Education teachers at State Senior High Schools in Rantau Selamat District. This type of research is field research. The results of the study indicate that 1) the pedagogical competence of Islamic Religious Education (PAI) teachers in the learning process at at State Senior High Schools in Rantau Selamat District, based on the results of the study that Islamic Religious Education (PAI) teachers at State Senior High Schools 1 and State Senior High Schools 2 Rantau Selamat have good and effective pedagogical competence in the learning process. 2) The work culture of Islamic Religious Education (PAI) teachers contributes to the formation of student character at process at State Senior High Schools in Rantau Selamat District, based on the results of research that the work culture of Islamic Religious Education (PAI) teachers at State Senior High Schools 1 and State Senior High Schools 2 Rantau Selamat plays a significant role in the formation of student character. 3) The implementation of pedagogical competence and the work culture of Islamic Religious Education (PAI) teachers at State Senior High Schools 1 and State Senior High Schools 2 Rantau Selamat is influenced by supporting and inhibiting factors. Supporting factors include teacher commitment and professionalism, principal support through academic supervision, a religious school environment, and adequate learning facilities, including digital media and comfortable classrooms